2015
DOI: 10.1007/s12035-015-9115-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Hyperglycemia in Patients with Brain Tumors: a Meta-Analysis

Abstract: Hyperglycemia has been associated with poor outcomes of patients with various diseases. There were several studies published to assess the association between hyperglycemia and prognosis of patients with brain tumors, but no consistent conclusion was available. We therefore performed a meta-analysis of available studies to evaluate the prognostic role of hyperglycemia in brain tumors. Several common databases were searched for eligible studies on the association between hyperglycemia and survival of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
9
1
Order By: Relevance
“…Previous meta-analyses have shown a poor survival associated with diabetes in patients with cancer, [ 8 ] including prostate, [ 9 ] pancreatic, [ 10 ] breast, [ 43 ] cervical, [ 44 ] colorectal, [ 45 ] lung, [ 46 ] and brain [ 47 ] cancer. Although the exact mechanisms underpinning worse outcomes in cancer patients with comorbid diabetes are unknown, hyperglycaemia and hyperinsulinemia have been proposed as possible biological pathways due to their roles in stimulating tumour growth [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous meta-analyses have shown a poor survival associated with diabetes in patients with cancer, [ 8 ] including prostate, [ 9 ] pancreatic, [ 10 ] breast, [ 43 ] cervical, [ 44 ] colorectal, [ 45 ] lung, [ 46 ] and brain [ 47 ] cancer. Although the exact mechanisms underpinning worse outcomes in cancer patients with comorbid diabetes are unknown, hyperglycaemia and hyperinsulinemia have been proposed as possible biological pathways due to their roles in stimulating tumour growth [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The distress prevalence in patients with intracranial tumor is not higher than that in patients with lung cancer (61.6%) [ 27 ] or bone marrow transplant patients (43.0%) [ 28 ]. The possible reasons could be the quick disease progression of a malignant brain tumor or early interventions by some of the clinical practitioners [ 17 , 29 31 ]. Fatigue, pain, anxiety, and depression are among the most troubling symptom associated with the prevalence of distress in brain tumor patients which will result in a poorer overall survival and decreased health-related quality of life (HRQoL) [ 17 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This raises concern due to the poor outcomes that have been associated with hyperglycemia and outcomes in brain tumor patients. Liu et al [31] conducted a recent meta-analysis on 2,168 patients and found that hyperglycemia was significantly associated with decreased overall survival, and this was irrespective of the cause of hyperglycemia.…”
Section: Standard Of Practicementioning
confidence: 99%
“…Historically, between 70-100% of patients with brain metastases have received steroid treatment during adjuvant RT, and between 10-50% after completion of RT [32][33][34][35][36][37]. Additionally, dexamethasone appears to have been the steroid of choice for these patients, with a starting daily dose of around 16 mg, but highly dependent on the patient clinical status [31,35,38]. Currently, clinical practice guidelines for patients with brain metastases recommend starting these patients on 4-8 mg/day of dexamethasone in the case of mild symptoms related to mass effect and reserving the higher dose of 16 mg/day for patients with severe symptoms [1].…”
Section: Standard Of Practicementioning
confidence: 99%